Aortic valve replacement during acute rheumatic fever. Issue 7 (July 1978) - Khan, A; Chi, S; Gonzalez-Lavin, L
Abstract : Emergency aortic valve replacement was performed during an attack of acute rheumatic fever in a 12-year-old black boy. He had an uneventful recovery and has remained asymptomatic 27 months after operation. In the light of this experience and that of others, one might conclude that the decision to operate on these patients should be based on the severity of the haemodynamic derangement rather than on the state of activity in the rheumatic process.